L’arte del kintsugi: frammento e totalità nell’estetica giapponese - Furlani, Simone (Scenari, 2024)
The Japanese art of kintsugi, that is the art of repairing broken or shattered porcelain with precious metals, transforms the shattering of an object into an opportunity for artistic expression. This essay examines the philosophical implications of this technique and shows why the underlying aesthetics is almost incompatible with many of the assumptions of Western aesthetics. Notably, the Buddhist background of this technique does not associate the idea of fragment with any symbolic or allegorical meaning, forbidden by the ultimate horizon of the becoming of reality and, therefore, also of art. From here, other fundamental notions of aesthetics such as those of creation, work of art, expression, etc., also take on a radically different meaning in the aesthetics of kintsugi than in the West.